In Vitro Growth Characteristic and Microbial Community Dynamic of Atlantic Salmon (Salmo Salar L) Gastrointestinal Tract in Relation to the Different Diet Formulations - Zarkasi, Kamarul Zaman; Taylor, Richard; Glencross, Brett D.; Abell, Guy C.J.; Tamplin, Mark L.; Bowman, John P. (2016)
In order to better understand microbial changes within the salmon gastrointestinal tract as determined at the dietary level, the microbial community dynamics were assessed within a simple in vitro growth model system. In this system the growth and composition of bacteria were monitored within diet slurries held under anaerobic conditions inoculated with salmon faecal samples. This system was assessed using total viable bacteria counts (TVC), automated ribosomal intergenic spacer analysis (ARISA) and 16S rRNA pair-end Illumina-based sequence analysis.